2020
DOI: 10.1101/2020.07.27.219501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenic mutations in LRRK2 sequester Rab8a to damaged lysosomes and regulate transferrin-mediated iron uptake in microglia

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) cause autosomal dominant Parkinson’s disease (PD) while polymorphic LRRK2 variants are associated with sporadic PD. PD-linked mutations increase LRRK2 kinase activity and induce neurotoxicity in vitro and in vivo. The small GTPase Rab8a is a LRRK2 kinase substrate and is involved in receptor-mediated recycling and endocytic trafficking of transferrin, but the effect of PD-linked LRRK2 mutations on the function of Rab8a are poorly understood. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 67 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…Previous work has demonstrated that TfR (Transferrin Receptor) is able to move to lysosomes in cells treated with LLOME and is required for an efficient recruitment of Gal3 after short exposure of the compound, triggering membrane repair [56]. Work from our lab (now in preprint: [58]) confirms that LRRK2 recruits RAB8A to dysfunctional lysosomes and shows that RAB8A is able to bring Transferrin and TfR to LRRK2-positive lysosomes.…”
Section: Accepted Articlesupporting
confidence: 58%
“…Previous work has demonstrated that TfR (Transferrin Receptor) is able to move to lysosomes in cells treated with LLOME and is required for an efficient recruitment of Gal3 after short exposure of the compound, triggering membrane repair [56]. Work from our lab (now in preprint: [58]) confirms that LRRK2 recruits RAB8A to dysfunctional lysosomes and shows that RAB8A is able to bring Transferrin and TfR to LRRK2-positive lysosomes.…”
Section: Accepted Articlesupporting
confidence: 58%
“…Immune signalling and lysosomal stress both induce translocation of LRRK2 and its phospho-substrates Rab8a and Rab10 on to stressed lysosomes in different cell types ( Eguchi et al, 2018 ). Interestingly Rab8a phosphorylation is increased by all pathogenic LRRK2 mutations ( Mamais et al, 2020 ). However, it is of interest that decreased Rab10 phosphorylation occurred only with LPS stimulation and not with zymosan treatment, suggesting that this effect is sensitive to TLR4 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 has also been shown to control repair of damaged endomembranes through its ability to phosphorylate Rab8A [ 26 , 27 ]. Treatment of cells with agents that stress lysosomes, promote Rab protein phosphorylation by LRRK2 [ 28 , 29 ]. Pathogenic LRRK2 also inhibits ciliogenesis in cholinergic interneurons through LRRK2 phosphorylated Rab10 forming a complex with RILPL1 [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%